Trade and economic development in Taiwan - Y. C. Jao (Intereconomics, 1976)
Taiwan's remarkable growth record has been the result of an outward-looking, export propelled development strategy. Recently unfavourable political and economic events have adversely affected Taiwan's economy. This article analyses the country's economic development and appraises its future prospects.
Keywords: 330; Taiwan